Layanan Bimbingan Konseling Islam Integratif Berbasis CBT Islami (Self Reflection) sebagai Pendekatan Psikologi Religius dalam Fenomena Fanatisme Pengajian Ibu-Ibu - Putri Julianto, Tiara Fitya Alfarizqa; Tajiri, Hajir; Arifin, Isep Zainal (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of Integrative Islamic Guidance and Counseling services based on Islamic Cognitive Behavioral Therapy (CBT) is important as a preventive and curative effort in addressing the phenomenon of fanaticism in women’s religious study groups. This study employs a qualitative approach, with primary data derived from library research. The findings indicate that the implementation of Integrative Islamic Guidance and Counseling services based on CBT using self-reflection techniques is carried out in a planned and systematic manner by adapting to the characteristics of the service recipients, namely women involved in religious study groups who exhibit tendencies toward religious fanaticism.The services can be delivered through group counseling or individual counseling, taking into account the level of the problem, group dynamics, and the client’s readiness to engage in the counseling process. During the implementation stage, counselors facilitate counseling sessions in a safe, non-judgmental environment that respects the clients’ religious values. Each session begins with the strengthening of the counseling relationship and a clear explanation of the session objectives so that clients understand the direction and benefits of the counseling services.